A novel method for the fabrication of porous Poly-Ether-Ether-Ketone using sodium chloride as a porogen - Siddiq, Abdur Rahman (2016)
A novel technique to manufacture porous Poly-Ether-Ether-Ketone (PEEK) scaffolds via a tapped-packing route of fabrication incorporating rounded salt beads had been investigated. The conventional salt leaching technique has been improved via the tapping-route in manufacturing porous PEEK structure that possesses adequate structural and mechanical properties. Three types of PEEK, Vicote, LT3 and LT1 were used as main material and rounded salt as a porogen. PEEK powder and the rounded salt were mixed in 6:1 mass ratio by applying tapping to 22 mm cylindrical die. 5 g of PEEK/salt beads mixture was packed through 8000 taps. Alternative mixing techniques also involved wet (using sprayed water) and dry mixing routes prior to the compaction. To solidify the PEEK and to obtain free-salt PEEK scaffolds, then sintering, dissolving and drying were applied. The results show that only a combination of the tapping route and the LT1 PEEK could secure porous PEEK scaffolds with acceptable and required characteristics in associated with the pore size range (main pores of (560 + 180) µm and windows of (204 + 41) µm) and shape, good interconnectivity, and homogenous and high porosity > 80%. It was also successfully integrated into a viable spinal PEEK cage implant via injection moulding.